The RANK/RANKL/OPG system and tumor bone metastasis: Potential mechanisms and therapeutic strategies - Zhang, Yan; Liang, Jingqi; Liu, Peilong; Wang, Qiong; Liu, Liang; Zhao, Hongmou (Frontiers in Endocrinology, 2022)
With the markedly increased diagnosis incidence of cancer in the population, tumor bone metastasis has become a frequent event in tumor patients. Commonly, healthy bone integrity is maintained by a delicate balance between bone formation and bone resorption. Unfortunately, many tumors, such as prostate and breast, often metastasize to the bone, and the alterations to the bone homeostasis can particularly favor tumor homing and consequent osteolytic or osteoblastic lesions. Receptor activator of NF-κB ligand (RANKL), its receptor RANK, and osteoprotegerin (OPG) were widely demonstrated to be involved in the regulation of the activation, differentiation, and survival of osteoclasts, which play critical roles in bone metastasis formation. Osteoclastic bone resorption significantly increases fracture risk, causes severe bone pain, and contributes to homing tumor cells in bone and bone marrow. Consequently, suppression of the RANK/RANKL/OPG system and osteoclastic activity can not only ameliorate bone resorption but may also prevent tumor bone metastases. This review summarizes the important role of the RANK/RANKL/OPG system and osteoclasts in bone homeostasis and its effect on tumor bone metastasis. More importantly, we will further introduce therapeutic strategies based on RANKL inhibition.